Expansion of polynomial Lie group integrals in terms of certain maps on surfaces, and factorizations of permutations. (12th January 2017) - Novaes, Marcel
Abstract: Using the diagrammatic approach to integrals over Gaussian random matrices, we find a representation for polynomial Lie group integrals as infinite sums over certain maps on surfaces. The maps involved satisfy a specific condition: they have some marked vertices, and no closed walks that avoid these vertices. We also formulate our results in terms of permutations, arriving at new kinds of factorization problems.